2006
DOI: 10.1111/j.1399-3054.2006.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA array analysis of stress‐induced gene expression in barley androgenesis

Abstract: Different aspects of androgenesis induction have been studied in detail, but little is known about the molecular mechanisms associated with this developmental switch. We have employed macroarrays containing 1421 expressed sequence tags covering the early stages of barley zygotic embryogenesis to compare the gene expression profiles of stress-induced androgenic microspores with those of uninucleate microspores as they progressed into binucleate stage during pollen development. Principal component analysis defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 75 publications
11
75
1
Order By: Relevance
“…In animal systems GSTs are expressed especially during embryonic and fetal growth where they support normal growth and development by reducing the levels of toxic organic hydroperoxides (Raijmakers et al 2001). A similar role may also be exercised during plant embryo development, as this ubiquitous group of proteins has been shown to increase during embryo development in a variety of culture systems (Vrinten et al 1999;Galland et al 2001;Maraschin et al 2006). BSO-mediated up-regulation of several GSTs may therefore be required for protecting the developing embryos against stress conditions, thereby ensuring successful growth and normal development.…”
Section: Antioxidant Responsementioning
confidence: 99%
“…In animal systems GSTs are expressed especially during embryonic and fetal growth where they support normal growth and development by reducing the levels of toxic organic hydroperoxides (Raijmakers et al 2001). A similar role may also be exercised during plant embryo development, as this ubiquitous group of proteins has been shown to increase during embryo development in a variety of culture systems (Vrinten et al 1999;Galland et al 2001;Maraschin et al 2006). BSO-mediated up-regulation of several GSTs may therefore be required for protecting the developing embryos against stress conditions, thereby ensuring successful growth and normal development.…”
Section: Antioxidant Responsementioning
confidence: 99%
“…First genes identified during induction of ME in barley encoded a lipid transfer protein-ECLTP, a glutathione-S-transferase-ECGST and arabinogalactan-like protein-ECA1 (Vrinten et al 1999), but further analysis revealed that only ECA1 was expressed specifically in embryogenic cells. In barley, Maraschin et al (2006), using microarrays containing ESTs (expressed sequence tags) identified a very distinct gene expression profile characteristic for embryogenic microspores. In comparison with developing pollen, in embryogenic microspores upregulation of genes involved in protein degradation (ubiquitin-conjugating enzyme, 20S proteasome subunit alpha-5 and alpha-2, 26S protease subunit-8, cysteine and aspartic protease and FtsH metalloprotease), starch and sugar hydrolysis (maltase, cell wall invertase), stress response (GTS, catalase), metabolism (alcohol dehydrogenase 3) and cell signalling (GTPase) was detected.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, YABBY5, ZML2, CURLY LEAF and ICE1 could play a direct role in microspore reprogramming. Previously in barley, Maraschin et al (2006) revealed that genes encoding an alcohol dehydrogenase 3 (ADH3), and proteolytic genes as a metalloprotease FtsH, a cysteine protease precursor, an aspartic protease, and a 26S proteasome regulatory subunit, could represent bio-markers for the embryogenic potential of microspores. These results indicated that metabolic changes and proteolysis have a critical role in the dedifferentiation phase of microspore embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among these stress-response genes, genes encoding glutathione S-transferases (GSTs) were overrepresented, representing a total of 2% of the up-regulated genes. GSTs are involved in oxidative stress response, pathogen attack and heavy metal toxicity (Marrs 1996) and the induction of members of the GST family during the initial steps of microspore embryogenesis has been described (Vrinten et al 1999;Maraschin et al 2006). With regard to heat shock proteins (HSPs), which have been reported to be highly expressed in microspores of rapeseed and tobacco upon heat shock and starvation (Cordewener et al 1995;Zarsky et al 1995;Smykal and Pechan 2000), only minor changes in the expression of the HSP genes were observed in this study.…”
Section: Expression Profile Associated With Stress Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation